Analysis of the applicability of steel 20MnCrS5 for gears of the domestic mobile machines - S. P. Rudenko; A. I. Valko; S. G. Sandomirskii (Литьë и металлургия, 2020)
Evaluation of applicability of 20MnCrS5 steel for gears of transmissions of mobile machines, manufactured according to European standard EN 10084 was carried out. Experimental and virtual simulation of hardenability of the steel according to the updated method was realized. The assessment of the applicability of 20MnCrS5 case-hardening steel for gears of the domestic mobile machines was made by the criterion of obtaining the cross section of the tooth structures with a hardness 32 HRC for core, 50 HRC for semi-conversion zone, 61–63 HRC for the diffusion layer excluding other physical and mechanical properties of steel.It is established that at the content of alloying elements close to the maximum limit, the use of this steel is possible for gears with a module up to 10 mm.